Literature Review: The Effect of Quranic Murottal Therapy on the Quality of Sleep of the Elderly - Afrischa Yusti Nabrita; Agus Sudaryanto (Indonesian Journal of Global Health Research, 2024)
Sleep is an important biological function. Sleep is very instrumental in the health of the brain which plays a role in many vital functions that are treated for survival it can help the body recover, inhibit energy, repair damaged tissue, improve immunity, and promote memory consolidation. Sleep patterns tend to change with age. Research examining the relationship between sleep quality and quality of life in elderly people shows that the better the quality of sleep the better the quality of life the elderly have. The purpose of this study was to Identify the Impact of Quranic Murottal Therapy on the Sleep Quality of the Elderly, Determine the Effectiveness of Duration and Frequency of Quranic Murottal Therapy, Analyze Factors Influencing the Elderly's Response to Quranic Murottal Therapy, Develop Recommendations for Implementing Quranic Murottal Therapy in Elderly Care. Literature review using electronic databases from national and international publications such as Google Scholar and PubMed, and literature review is a research methodology used ranging from 2019 - 2023. The keywords from Google Scholar are Qur'an Murottal Therapy, sleep quality, elderly, and sleep disorders in the elderly, as well as from PubMed with the keywords "Randomized Control" OR "Clinical Trial" AND "Murottal Al - Qur'an" AND "Elderly" AND "Sleep Quality" OR "Insomnia". After a preliminary literature search on Google Scholar and PubMed, 225 articles with the same title were found, 80 of which were discarded because they were less relevant to the issue of the effect of Qur'anic murottal therapy on the quality of sleep of the elderly. The requirements were met by 10 full text articles. Conclusion: The elderly can improve their sleep quality with Qur'an Murottal Therapy.